Occupational stress, mental health and gender among higher education teachers: integrative review - Pinho, Paloma de Sousa; Freitas, Aline Macedo Carvalho; Patrão , Ana Luísa; Aquino, Estela M L (Saúde e Sociedade, 2024)
The teacher’s work in universities has been marked by exhaustive overload with intensive and precarious work conditions. Furthermore, studies regarding gender, health, and teacher’s work are still scarce. In this article, we aimed at identifying and critically evaluating the scientific evidence regarding occupational stress and mental health among higher education teachers from a gender perspective. We performed an integrative review of literature by searching on PubMed, SciELO, and LILACS, between May and June 2019, from combinations of the indexed descriptors: occupational stress; mental disorder; mental health; higher education; faculty; universities; and the keywords: faculty teacher; faculty teachers; university teacher; university teachers; academic setting; academic settings. The results indicate that occupational stress is common in universities, with teachers showing increasing dissatisfaction and higher prevalences of mental disorders and depressive symptoms. The need for accountability of educational managers is evident. Gender perspective was absent or scarce in the scientific literature revised. Concentrating on measurements to improve the quality of work in universities making them an equally pleasant space for men and women is needed.